Noncompletion in Pediatric Rheumatology Fellowships - Riebschleger, Meredith (The Accreditation Council for Graduate Medical Education, 2014)
BACKGROUND: One challenge facing the health care workforce is a paucity of pediatrics subspecialists. No prior studies have investigated fellowship noncompletion as an influence of the subspecialty workforce. OBJECTIVE: We sought to determine the noncompletion rate for pediatric rheumatology fellowships and to identify demographic characteristics associated with noncompletion. METHODS: A retrospective cohort study of all trainees entering US pediatric rheumatology fellowship programs between 1997 and 2007 was performed. American Board of Pediatrics tracking data were used to determine completion status (completer or noncompleter) for each trainee. Completers were compared with noncompleters, using the independent variables sex, medical school location, and age. The noncompletion rate was calculated overall and individually. Program size was examined as a predictor of nonompletion rate. Data analysis used χ(2) tests, Kruskal-Wallis tests, and Spearman correlation. RESULTS: The cohort included 182 trainees from 28 pediatric rheumatology fellowship programs. Program size ranged from 1 to 18 trainees. The overall noncompletion rate was 16%. Male fellows, especially male international medical graduates, were more likely to be noncompleters. Noncompletion rates varied among programs: 15 programs had noncompletion rates of 0% and 4 programs had noncompletion rates of 50% or higher. Program size was not associated with noncompletion rate. CONCLUSIONS: During the study period, 1 of 6 pediatric rheumatology fellows did not complete training. Noncompletion was concentrated in a small number of programs. Further research should investigate noncompletion across specialties, identifying the causes of noncompletion at the individual, program, and specialty levels to inform future interventions to improve fellowship completion.